Behavioral determinants of electricity consumption in dutch dwellings - Bedir, Merve; Hasselaar, Evert; Itard, Laure (A+BE | Architecture and the Built Environment, 2018)
Following the sensitivity analysis on heating energy consumption in Chapter 3, Chapter 4 is an analysis on the determinants of electricity consumptions in Dutch dwellings. The OTB sample was used for analysis, and it was validated with analysis of the WoON sample. The work was published as: This Chapter deals with the Research Question II of this thesis: (Chapter 1, Section 3, pg. 16-17) “II. What is the influence of lighting and appliance use on the total electricity consumption in dwellings?" The sub-questions are: 1. What are the main direct and indirect determinants of electricity consumption? (Direct determinant: such as number of appliances and duration of appliance use … Indirect determinant: such as household size, dwelling size, dwelling type …) 2. How much of the variance in electricity consumption in dwellings can be explained by direct and indirect determinants?” The research reported in this Chapter was conducted by Bedir. The data was collected by a questionnaire prepared by Guerra Santin and Bedir, using OTB’s means of data collection. The analysis was done, and the paper was written by Bedir. The co-authors commented on the drafts and gave advise on the structure, and the content of the paper. The co-authors have given their permission to include the paper in the thesis.